A Hora do Soninho: uma proposta de intervenção junto a creches - Bertolucci, Giulia Maria [UNESP] (2015)
The claim that the quality of sleep is an important indicator of health and well-being in children is supported by numerous evidences. They show that their compromise is associated with problems such as anxiety, depression, preoccupations and tension. The current project aims to develop an intervention to improve the “nap time” in child day care center.